Problematics of proving the fact of occupational TB in health care workers. - G. M. Daragan; T. Yu. Krushinska; N. V. Hrankina; O. V. Vorontsova; D. O. Stepanskiy (Medičnì Perspektivi)
The incidence of tuberculosis in medical personnel in the Dnipropetrovsk region, incl. TB facilities, was analyzed for the period from 2008 to 2017. Occupational TB is an important indicator of infection control efficacy in health care facilities. Despite reducing trend of incidence in entire population and medical workers, their morbidity rates exceeded Ukrainian average ones by 25.0% and 2.5 times, respectively. There is about one and a half thousand employees in TB facilities of Dnipropetrovsk region. Their TB incidence rate was almost 5 times (p≤0.05) higher than in employees of other health care institutions and 6.6 times (p≤0.05) exceeded incidence of tuberculosis in community. In TB facilities, the highest incidence was registered among nurses – 506.8 per 100000. Non-medical workers have the second rank of incidence (409.4 per 100000). They did not contact TB patients directly, but inhaled air containing Mycobacterium tuberculosis. The incidence of TB in doctors and hospital attendants was lower – 384.6 and 357.1 per 100000, respectively. Nurses prevailed among TB-ill medical personnel of TB facilities – 41±3,4%. Hospital attendants had morbidity of 24±5,4%, non-medical stuff – 22±5,2%, doctors – 13±4,%. The confirmation of healthcare workers’ occupational TB cases is complicated. Taking info account that this infection is widely spread in community it is necessary to reveal active and latent tuberculosis infection with the quantiferon test and other modern methods, as well as to carry out genotyping of mycobacterium tuberculosis for finding epidemiological links in nosocomial TB transmission. To reduce the risks of occupational disease, it is important to carry out trainings on TB infection control for medical personnel and support staff.